ANALISIS PENGGUNAAN SISTEM AKTUATOR PNEUMATIK BERTENAGA SURYA TERHADAP KINERJA MESIN PEMOTONG NANAS - Rafil, Rafil Arizona; Iqbal, M; Kurnia, Kurnia Hastuti; Sehat, Sehat Abdi Saragih; Shandy, Shandy Kurniadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The main objective of this research is to determine the overall performance value of the pneumatic actuator system on a solar-powered pineapple cutting machine. The research methods used are literature study and experimental laboratory. The laboratory experimental method is very suitable to be applied to post-harvest agricultural machines with a small capacity where the research is only focused on the success of the actuator system in carrying out pineapple cutting movements automatically by utilizing pressurized air coming from the compressor. The variation in air pressure for the pneumatic actuator is set at the air pressure, namely 3, 4, and 5 Bar. The actual peeling capacity using air pressure of 3 Bar resulted in 160 pineapple cutting/per hour, 170 fruit/per hour for 4 Bar, 173 bar for 5 bar, and 173 fruit/per hour manually. The efficiency of peeling pineapple manually was 82.8% while using a pneumatic actuator system it was 70.6%. The DC electrical energy storage capacity required for the pneumatic actuator drive system is a battery with a capacity of 80 Ah 12 v which is supplied by electrical energy originating from a 200 Wp solar panel. Solar panels of this size are sufficient to equip a pneumatic actuator system for stripping with capacity of 1 hour/day. The results of this study are expected provide the latest reference for determining the optimal productivity of solar-powered pineapple cutting machines today.